2013
DOI: 10.1155/2013/343909
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Mechanical Strain and Hydroxyapatite/Collagen Composite on Osteogenic Differentiation of Rat Bone Marrow Derived Mesenchymal Stem Cells

Abstract: Mesenchymal stem cells (MSCs) represent a promising source for bone repair and regeneration. Recent lines of evidence have shown that appropriate strain could regulate the osteogenic differentiation of MSCs. Our previous study demonstrated that hydroxyapatite/collagen (HA/Col) composite also played an important role in the osteogenic differentiation of MSCs. The aim of this study is to investigate the effects of mechanical strain and HA/Col composite on the osteogenic differentiation of rat bone marrow derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…These results suggest that COL is a suitable cell expansion matrix to retain high osteogenic differentiation potential of MSC and provide a synergistic effect in promoting osteogenic differentiation in the presence of induction factors prior to in vivo administration. Similar increase in osteogenic differentiation on COL surface was also reported by Linsley et al and others [ 21 , 22 , 24 26 , 28 , 47 ]. Although chondrogenic differentiation is an important property of MSC, it was not tested in the current study as chondrogenic differentiation in vitro is usually performed as a pellet culture where there was no scope for cell to cell-culture-surface contact.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results suggest that COL is a suitable cell expansion matrix to retain high osteogenic differentiation potential of MSC and provide a synergistic effect in promoting osteogenic differentiation in the presence of induction factors prior to in vivo administration. Similar increase in osteogenic differentiation on COL surface was also reported by Linsley et al and others [ 21 , 22 , 24 26 , 28 , 47 ]. Although chondrogenic differentiation is an important property of MSC, it was not tested in the current study as chondrogenic differentiation in vitro is usually performed as a pellet culture where there was no scope for cell to cell-culture-surface contact.…”
Section: Discussionsupporting
confidence: 89%
“…Although the matrix rigidity and elasticity were not tested in our study, the results show that differential mechano-sensing and signaling was promoted in cells cultured on different matrices. Even though other studies have shown the usefulness of COL and FBN as suitable extracellular matrix for osteogenic differentiation of MSC [ 21 , 22 , 24 26 , 28 , 47 ], our study specifies their suitability in enhancing cell attachment, migration, cell survival and maintaining their self-renewal and differentiation potential. Taken together, our results suggest that COL might be employed as a matrix during in vitro cell expansion to maintain their osteogenic differentiation potential and coating in vivo scaffolds for increased cell adhesion, proliferation, survival during stress conditions and migration.…”
Section: Discussionmentioning
confidence: 86%
“…82 In addition, mechanical strain along with HA addition had a positive effect on mRNA expression of ALP and matrix mineralization. 82 Several studies have shown the significance of matrix stiffness on ALP expression. Chattergee et al detected no mineralization in MC3T3-E1 osteoblasts encapsulated in polyethylene glycol (PEG) gels with <100 kPa compressive modulus.…”
Section: Discussionmentioning
confidence: 93%
“…In addition to the application in cardiac cell mechanobiology, it is also suggested to use this device in the other mechanosensitive cells culture. For example, a mechanical strain of 5% is considered as threshold for enhancing the osteogenic differentiation [15,16]. Thus, to mechanically stimulate the bone cells, a preferable loading of 20 kPa is suggested to be applied in our device, which will result in an out-of-plane displacement of 170 μm.…”
Section: Discussionmentioning
confidence: 99%
“…In different applications, the thresholds of mechanical strain for enhancing specific differentiations are different. For instance, Gopalan et al found that the cardiac differentiation was enhanced under the stretching strain of 10% [14], while a mechanical strain of 5% is considered as a threshold for eliciting the osteogenic differentiation [15,16]. However, no mathematical basis has existed to quantitatively determine the applied loading so as to achieve a needed strain in specific cell culture experiment.…”
Section: Introductionmentioning
confidence: 99%